Odpowiedź :
x-y=3
3(x-1)=2x+y
x=3+y
3x-3=2x+y
x=3+y
3(3+y)-3=2(3+y)+y
x=3+y
9+3y-3=6+2y+y
x=3+y
9+3y-3-3y=6
x=3+y
6=6
przykładowymi parami rozwiązań mogą być x=9 y=6
bo
9-6=3
3(9-1)=2*9+6
24=24
oraz x=6 y=3
6-3=3
3(6-1)=2*6+3
15=15
Przykład 2
x+y=2
2(x-1)=x+3
x=2-y
2x-2=x+3
x=2-y
2(x-1)=x+3
x=2-y
2(2-y)-1=(2-y)+3
x=2-y
4-2y-1=2-y+3
x=2-y
-2y+y=3-3
y=0
x=0
3(x-1)=2x+y
x=3+y
3x-3=2x+y
x=3+y
3(3+y)-3=2(3+y)+y
x=3+y
9+3y-3=6+2y+y
x=3+y
9+3y-3-3y=6
x=3+y
6=6
przykładowymi parami rozwiązań mogą być x=9 y=6
bo
9-6=3
3(9-1)=2*9+6
24=24
oraz x=6 y=3
6-3=3
3(6-1)=2*6+3
15=15
Przykład 2
x+y=2
2(x-1)=x+3
x=2-y
2x-2=x+3
x=2-y
2(x-1)=x+3
x=2-y
2(2-y)-1=(2-y)+3
x=2-y
4-2y-1=2-y+3
x=2-y
-2y+y=3-3
y=0
x=0